P3.163 Differences between women attending specialist sexual health clinics and those attending general practices: implications for targeting sti testing. (8th July 2017) - Edelman, Natalie; Mercer, CM; Cassell, J; Visser, RO De
Abstract : Introduction: In Britain sexual health interventions are increasingly provided in community settings such as General Practices (GPs), while Genito-Urinary Medicine clinics have largely been replaced by Sexual Health and for Contraception clinics (SHACs). This study compared women attending GPs with those attending SHAC in an urban setting to investigate how much these populations differ and to assess the extent of sexual risk behaviour in GP populations. Methods: A convenience sample of women aged 16–44 years attending GP and SHAC services in the city of Brighton and Hove was invited to complete a short questionnaire about socio-demographic, psychosocial and sexual behavioural factors. Results: 1288 participated from GPs and 552 women from SHAC. 11.2% of GP participants and 3.4% of SHAC participants (p<0.0001) reported no male sexual partners in the last year. GP participants were less likely than SHAC participants to report 2 or more male sexual partners in the last year (2PP) (21.5% versus 60.9% p<0.0001) and to report non-use of condoms with two partners in the last year 6.9% versus 24.2% p<0.0001.These associations remained after adjusting for the smaller proportion of women≤24 years among GP participants compared to SHAC (21.7% v. 44.5% p<0.0001). Binge drinking alcohol in the last week was associated with 2PP (p<0.0001) and was more common among SHAC participants≤24 years than GP participants≤24 years (49.8% versus 37.9% p=0.009). However, it did not differ across sites for women aged 25–44 years (33.3% versus 36.3% p=0.362). Conclusion: Although women attending GPs are less likely than those attending SHAC to report sexual risk behaviour in the last year, a substantial minority may benefit from sexual health promotion, STI testing and alcohol awareness. This supports the development of a risk prediction tool to target sexual health and adjunct interventions in community settings among women aged 16–44 years.